2018
DOI: 10.5194/hess-2018-509
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of glacier loss on annual basin water yields

Abstract: Abstract. We couple a glacier flow model to a simplified landscape model to investigate the effects of glacier dynamics, climate, and vegetation succession on annual basin runoff during glacier retreat. Basin runoff initially increases as water is released from glacier storage but eventually decreases to below preretreat levels due to increases in evapotranspiration and altitudinal losses in precipitation. Peak basin runoff and the time to peak basin runoff are primarily determined by glacier dynamics, with sh… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…On the other hand, a study by Carnahan et al. (2018) identified through glacier flow modeling that glacier dynamics (characterized by glacier response times, linked primarily to climate and slope) and landscape evolution (i.e., vegetation succession after deglaciation) had a roughly equal impact on basin runoff in response to glacier retreat. Together, these findings indicate that peak water is likely to occur at different times in different regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a study by Carnahan et al. (2018) identified through glacier flow modeling that glacier dynamics (characterized by glacier response times, linked primarily to climate and slope) and landscape evolution (i.e., vegetation succession after deglaciation) had a roughly equal impact on basin runoff in response to glacier retreat. Together, these findings indicate that peak water is likely to occur at different times in different regions.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Moore et al (2009) identified for Western North America that northern basins with larger glaciers still show increasing runoff while basins with smaller glaciers further south have already passed peak water. On the other hand, a study by Carnahan et al (2018) identified through glacier flow modeling that glacier dynamics (characterized by glacier response times, linked primarily to climate and slope) and landscape evolution (i.e., vegetation succession after deglaciation) had a roughly equal impact on basin runoff in response to glacier retreat. Together, these findings indicate that peak water is likely to occur at different times in different regions.…”
mentioning
confidence: 99%